Is increased surveillance for asymptomatic syphilis in an HIV outpatient department worthwhile?. Issue 3 (1st June 2003) - Winston, A; Hawkins, D; Mandalia, S; Boag, F; Azadian, B; Asboe, D
Abstract : Objectives: Syphilis outbreaks have recently been reported in the United Kingdom, some of which have included cohorts of HIV positive individuals. As a result we commenced 3 monthly screening of syphilis serology (STS) for HIV positive patients having routine follow up blood tests. We assessed if there was an increased number of individuals being screened and also whether the screening programme was diagnosing early cases of syphilis. Methods: Data from a 1 year period following introduction of screening (May 2001) were analysed and compared with data from the same period last year. The case notes of patients with a positive VDRL were reviewed to establish, firstly, whether these represented new diagnoses and, secondly, whether patients were asymptomatic at the time of screening. Results: 2670 patients had at least one CD4 count measured in the period (surrogate for patients having routine bloods). Of these, 2266 patients had STS performed (85%). 38 patients had a positive VDRL. Of these, 20 were confirmed as having early syphilis which was asymptomatic at the time of screening. Six asymptomatic cases were also confirmed with newly positive TPPAs and a negative VDRL. These 26 asymptomatic cases represent 29% of all cases of early syphilis diagnosed in our department and 50% of cases in the HIV positive cohort. Conclusion: With intensive surveillance significant numbers of cases of asymptomatic early syphilis are being identified in a group of HIV individuals under routine follow up, at an earlier stage than would otherwise have been the case. This presents an opportunity to intervene not only to prevent clinical illness but also to institute infection control measures.